2017
DOI: 10.1007/s11666-017-0555-4
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Feedstock Plasma Spraying: An Emerging Process for Advanced Thermal Barrier Coatings

Abstract: Liquid feedstock plasma spraying (LFPS) involves deposition of ultrafine droplets of suspensions or solution precursors (typically ranging from nano-to submicron size) and permits production of coatings with unique microstructures that are promising for advanced thermal barrier coating (TBC) applications. This paper reviews the recent progress arising from efforts devoted to development of high-performance TBCs using the LFPS approach. Advancements in both suspension plasma spraying and solution precursor plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The suspension plasma spray (SPS) process is considered as a technique that enables variations of thermally sprayed coatings e.g., from highly dense and vertically cracked (DVC) to porous, feathery, and columnar microstructures [1]. There is a growing demand for yttria-stabilized zirconia (YSZ) suspensions to deposit thermal barrier coatings (TBC), either to generate the main TBC ceramic layer or as a repair method [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suspension plasma spray (SPS) process is considered as a technique that enables variations of thermally sprayed coatings e.g., from highly dense and vertically cracked (DVC) to porous, feathery, and columnar microstructures [1]. There is a growing demand for yttria-stabilized zirconia (YSZ) suspensions to deposit thermal barrier coatings (TBC), either to generate the main TBC ceramic layer or as a repair method [2].…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing demand for yttria-stabilized zirconia (YSZ) suspensions to deposit thermal barrier coatings (TBC), either to generate the main TBC ceramic layer or as a repair method [2]. In both cases, the preferred microstructure contains large globular pores and connected cracks that can potentially yield high strain tolerance and low thermal conductivity [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…An overwhelming proportion of SPS studies reported so far have been exclusively driven by interest in TBCs. This is attributable to the use of nano or sub-micron sized feedstock enabling realization of a unique columnar microstructure similar to the electron beam physical vapor deposition (EB-PVD) processed TBCs [50]. It may also be mentioned that the deposition rates achievable by SPS are significantly faster than in the case of EB-PVD and the former is, therefore, also deemed more economical [51].…”
Section: Sps Coatings For Tbc Applicationsmentioning
confidence: 99%
“…Suspension plasma spray (SPS) process is considered as a technique that enables variations of thermally sprayed coatings e.g., from highly dense and vertically cracked (DVC) to porous, feathery and columnar microstructures [1]. There is a growing demand for yttria-stabilized zirconia (YSZ) suspensions to deposit thermal barrier coatings (TBC), either to generate the main TBC ceramic layer or as a repair method [2].…”
Section: Introductionmentioning
confidence: 99%